A new species of Tomarus Erichson, 1847 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini), with a key to the species in Colombia - López-García, Margarita M.; Gasca-Álvarez, Héctor J.; Amat-García, Germán (Zootaxa, 2014)
A new Tomarus Erichson, 1847 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) species is described from western Colombia. The new species is compared with Tomarus laevicollis (Bates, 1888) from Central America. An identification key is also provided to the species occurring in the country.